Pelestarian Batik Tulis Bakaran oleh Pangrajin di Desa Bakaran Kabupaten Pati - Suyudi, Anggit Alfi; Trinugraha, Yosafat Hermawan; Rahman, Abdul (IJTIMAIYA: Journal of Social Science and Teaching, 2023)
Preservation of Burnt Written Batik by Craftsmen in Bakaran Village, Pati Regency. The purpose of this research is to find out the various efforts made by batik craftsmen in preserving Bakaran batik in Bakaran Village, Juwana District, Pati Regency.  The research method used is descriptive qualitative, with a case study approach.  The research sample is Bakaran batik craftsmen, government, employees, and consumers.  The results showed that the efforts of craftsmen in preserving Bakaran's batik had been carried out in various ways, namely promoting by participating in exhibitions, providing training and motif development, making batik educational tours, and forming batik groups.  Based on the analysis conducted using the AGIL concept from Parsons structural functionalism theory, it shows that the efforts made by batik craftsmen in preserving Bakaran batik are in accordance with the AGIL concept, namely: Adaptation (A) developing motifs;  making various products from batik, Goal attainment (G) promoting batik through exhibitions;  making batik educational tours, Integration (I) the formation of batik groups as a relationship between fellow craftsmen and also with the government, Latency (L) the process of inheriting batik knowledge by providing training to the younger generation and the community.  With these various forms of effort, it can be said that the preservation of Bakaran's written batik carried out by craftsmen has been going quite well, although there are still some shortcomings.  Therefore, conservation efforts must be further improved so that later it will get better results.